Case report: A new pathogenic variant of LRBA deficiency with a complex phenotype and Rosai-Dorfman disease - Fabozzi, Francesco; De Vito, Rita; Gaspari, Stefania; Leone, Fabrizio; Delvecchio, Maurizio; Agolini, Emanuele; Galaverna, Federica; Mastronuzzi, Angela; Pagliara, Daria; De Ioris, Maria Antonietta (Frontiers in Immunology, 2022)
We reported a new pathogenic variant of LRBA deficiency with a complex phenotype -neonatal diabetes, very early onset inflammatory bowel disease and polyarthritis- who presented a lymph node enlargement. A Rosai Dorfman's disease (RDD) was confirmed. The occurrence of RDD lesion in LRBA-deficiency has never been reported so far.